Dupuytren's Contracture Cosegregation with Limb-Girdle Muscle Dystrophy - Baiba Lace; Inna Inashkina; Ieva Micule; Inta Vasiljeva; Maruta Solvita Naudina; Jurgis Strautmanis; Janis Stavusis; Eriks Jankevics (Case Reports in Neurological Medicine)
Limb-girdle muscular dystrophies (LGMDs) is a heterogeneous group of muscular dystrophies that mostly affect the pelvic and shoulder girdle muscle groups. We report here a case of neuromuscular disease associated with Dupuytren's contracture, which has never been described before as cosegregating with an autosomal dominant type of inheritance. Dupuytren's contracture is a common disease, especially in Northern Europe. Comorbid conditions associated with Dupuytren's contracture are repetitive trauma to the hands, diabetes, and seizures, but it has never before been associated with neuromuscular disease. We hypothesize that patients may harbor mutations in genes with functions related to neuromuscular disease and Dupuytren's contracture development.